Considering gender and the WTO services negotiations - Meg Jones (South Centre, 2006)
The objective of this paper is to raise awareness amongst trade negotiators from developing and least developed countries of the inter-relationship between gender and trade in services issues. The context is the negotiations within the General Agreement on Trade in Services (GATS) under the auspices of the World Trade Organization (WTO). Whilst the purpose of this paper is not to provide specific solutions, key issues are highlighted and suggestions made that require further investigation and discussion in approaching the linkages between gender and GATS. Possible routes forward are captured in the recommendations section of the paper. The analysis of the paper rests on two factors: the critical role of women in economic and human development; and recognition of gender stereotyping as a determinant in the division of labour both in the workplace and in the home. Notions surrounding 'women's work' and 'men's work' continue to contribute to occupational segregation: women form the bulk of employees in call centres and catering; most architects and engineers are male. Household relations entrust responsibility for the collection of water, childcare, the care of the sick and the elderly, predominantly with women and the girl-child.
Keywords: 300; GATS; Dienstleistungshandel; Entwicklung; Geschlecht; Kritik; Entwicklungsländer; Vierte Welt